COPING STRATEGIES TOURISM WORKER HOUSEHOLD DURING COVID-19 PANDEMIC, EVIDENCE IN GIANYAR, BALI - Budiningsih, Ni Ketut Ketut; Saraswati, Putu Tara (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.12.TAHUN.2023, 2023)
This study analysis the coping strategies of the tourism worker household during Covid-19 pandemic in Gianyar, Bali. The data of this study comes from the answer of the online survey. The respondent is the tourism worker from Gianyar regency in Bali. The data estimates using Linear Probability Model with fixed effects to solve endogeneity problem between urban area and rural area. Education household head are the important characteristics of the household head which affects the coping strategies of the household. Further, child adult ratio and social network are also the important characteristics of the household which determine the coping strategies of the household. Social network important in Indonesia. Consequently, in promote the policy, the government can utilize the social group in the community. There are limited number of research analyses the coping strategies of the Gianyar tourism worker. Further, the previous researches use qualitative analysis or descriptive statistics. This study contributes on the research in coping strategies of the Gianyar tourism worker and estimates using econometrics analytical tool.